2022
DOI: 10.1007/s00277-022-04841-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction of CMV reactivation after allogeneic stem cell transplantation using five non-HLA immunogenetic polymorphisms

Abstract: Despite advances in the understanding of the pathophysiology of cytomegalovirus (CMV) infection, it remains as one of the most common infectious complications after allogeneic hematopoietic stem cell transplantation (allo-HSCT). The aim of this study was to determine the genotype of cytokines and chemokines in donor and recipient and their association with CMV reactivation. Eighty-five patients receiving an allo-HSCT from an HLA-identical sibling donor were included in the study. Fifty genes were selected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Onset of CMV reactivation is typically reported within 28 to 72 days after transplantation; affecting 40–60% of bone marrow allogeneic transplant recipients and may progress to severe CMV-related diseases [ 7 9 ]. It is worth mentioning that variation in CMV reactivation definition among clinical studies may contribute to the wide ranges of CMV reactivation rates seen in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Onset of CMV reactivation is typically reported within 28 to 72 days after transplantation; affecting 40–60% of bone marrow allogeneic transplant recipients and may progress to severe CMV-related diseases [ 7 9 ]. It is worth mentioning that variation in CMV reactivation definition among clinical studies may contribute to the wide ranges of CMV reactivation rates seen in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Often considered a homeostatic chemokine, inflammatory activities have been attributed to SDF-1 (CXCL12) ( 7 ). Polymorphisms in the CXCL12 gene are associated with the occurrence of CMV reactivation after allogeneic hematopoietic stem cell transplantation ( 8 ), whereas elevated plasma levels identify poor immune reconstitution in HIV patients ( 9 ). SDF1 mainly signals via the CXCR4 receptor, and it has been shown that CMV enhances SDF-1/CXCR4 signaling during infection through the product of the UL111A gene (which encodes a viral ortholog of human IL-10) ( 10 ).…”
mentioning
confidence: 99%